Взаємозв’язок рівня фетуїну-А з клінічними особливостями хворих на ішемічну хворобу серця, асоційовану з залізодефіцитом - Коновалова, М. О.; Михайловська, Наталія Сергіївна; Konovalova, M. O.; Mykhailovska, N. S. (Запорізький державний медико-фармацевтичний університет, 2023)
Мета роботи – оцінити взаємозв’язок рівня фетуїну-А з показниками клінічної гемограми, ферокінетики, вегетативними та структурно-функціональними змінами міокарда у хворих на ішемічну хворобу серця (ІХС), асоційовану з залізодефіцитом (ЗД) різних ступенів. Матеріали та методи. Обстежили 90 хворих на ІХС: стабільну стенокардію напруги ІІ–ІІІ ФК (35 чоловіків, 55 жінок) віком 69 (61; 72) років. У І групу (n = 16) залучили пацієнтів із залізодефіцитною анемією (ЗДА) легкого та середнього ступенів тяжкості, у ІІ (n = 15) – з абсолютним латентним ЗД, у ІІІ (n = 14) – із функціональним латентним ЗД; IV (контрольна) група (n = 45) – хворі на ІХС без ЗД. Фізіологічну концентрацію фетуїну-А визначили у 15 умовно здорових осіб. Оцінили результати ехокардіоскопії, моніторування електрокардіограми за Холтером та їхній зв’язок із рівнем фетуїну-А. Результати. У хворих на ІХС, що асоційована з ЗД, визначили зменшення концентрації фетуїну-А, прямо пропорційне ступеню прогресування сидеропенії. Кореляційний аналіз показав взаємозв’язок рівня фетуїну-А з концентрацією феритину та насичення трансферину залізом у групі хворих на ЗДА, а також кількістю еритроцитів – у хворих із функціональним ЗД. The aim of the study: to assess the relationship between the level of fetuin-A and features of clinical hemogram, ferrokinetic parameters, vegetative and structural-functional changes of the myocardium in patients with coronary artery disease (CAD) associated with different stages of iron deficiency (ID). Materials and methods. The study involved 90 patients with CAD: stable angina pectoris II–III FC (35 men and 55 women, age – 69 (61; 72)). All patients were divided into 4 clinical groups depending on the parameters of iron metabolism and hemogram: I (n = 16) – patients with absolute ID, II (n = 15) – with latent ID, III (n = 14) – with functional ID; IV (n = 45) – patients CAD without iron metabolism disorders. The physiological concentration of fetuin-A was determined in 15 conditionally healthy people. The results of echocardioscopy, Holter ECG monitoring and their relationship with the level of fetuin-A were analyzed. Results. In patients with CAD associated with various stages of ID, there is a decrease in the concentration of fetuin-A in direct proportion to the degree of progression of sideropenia was established. It was established that there is a relationship between the level of fetuin-A and the concentration of ferritin and transferrin saturation for patients with absolute ID as well as the number of erythrocytes in patients with functional ID. It was established that there is a relationship between the level of fetuin-A and PWd (rs = -0.60, p < 0.05) for patients with absolute ID; for patients with latent ID – with the E/A ratio (rs = +0.66, p < 0.05). In patients with absolute ID and latent ID a number of correlations between fetuin-A level and heart rate variability indicators in active and passive periods was established. The presence of a low level of fetuin-A in patients with CAD and ID increased the risk of left ventricular hypertrophy by 1.5 times, left ventricular diastolic dysfunction by 1.6 times, autonomic dysfunction by 2.14 times in the active period and 1.95 times in the passive period.
The relationship between fetuin-A level and the clinical features of patients with coronary artery disease associated with iron deficiency
Коновалова М. О. - ORCID ID: 0000-0002-3387-5802; Михайловська Н. С. - ORCID ID: 0000-0001-6781-9406.
Keywords: ішемічна хвороба серця; залізодефіцит; анемія; фетуїн-А; ремоделювання серця; вегетативна дисфункція; ризик; coronary artery disease; iron deficiency; anemia; fetuin-A; cardiac remodeling; autonomic dysfunction; risk